1982
DOI: 10.1111/j.1365-2125.1982.tb01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of beta‐adrenoceptor antagonists in asthmatic patients.

Abstract: 1 Bronchial smooth muscle, skeletal muscle and cardiac 13-adrenoceptor antagonism have been compared in twelve asthmatic patients after three 0-adrenoceptor antagonists at two dose levels. The non-selective antagonist propranolol (40 and 160 mg), the non-selective antagonist with partial agonist activity pindolol (5 and 20mg) and the Pl-selective antagonist atenolol (50 and 200 mg) were studied on separate occasions. 2 Six placebo days were used in this double-blind crossover study to allow interpretation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
4

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 25 publications
(31 reference statements)
0
13
0
4
Order By: Relevance
“…When administered acutely, they increased AR, whereas chronically, they significantly decreased the maximal constrictor response to methacholine. Whereas the acute effects of nadolol and carvedilol are in line with the reported effects of single-dose administration of nonselective ␤-blockers such as propranolol or timolol to asthmatic subjects (33) and various animal models (34)(35)(36)(37), the long-term effects of these drugs on airway responsiveness represent a major finding that could have therapeutic implications. It is noteworthy that a similar timedependent opposite effect has also been observed with certain ␤-blockers in the treatment of CHF.…”
Section: Effect Of ␤-Ar Ligands On Airway Responsiveness To Methacholmentioning
confidence: 61%
“…When administered acutely, they increased AR, whereas chronically, they significantly decreased the maximal constrictor response to methacholine. Whereas the acute effects of nadolol and carvedilol are in line with the reported effects of single-dose administration of nonselective ␤-blockers such as propranolol or timolol to asthmatic subjects (33) and various animal models (34)(35)(36)(37), the long-term effects of these drugs on airway responsiveness represent a major finding that could have therapeutic implications. It is noteworthy that a similar timedependent opposite effect has also been observed with certain ␤-blockers in the treatment of CHF.…”
Section: Effect Of ␤-Ar Ligands On Airway Responsiveness To Methacholmentioning
confidence: 61%
“…39 Comparative studies have shown, though, that /3-blocking compounds with partial agonist activity, 40 0,-selectivity, 41 -42 and a-adrenergic blocking actions 43 are less likely to increase airways resistance in asthmatics than propranolol. /3,-Selectivity, however, is not absolute and may be lost with high therapeutic doses as shown with atenolol and metoprolol.…”
Section: Adverse Noncardiac Side Effects Related To £-Adrenergic Recementioning
confidence: 99%
“…Binding studies show that approximately 70% of pulmonary ␤-ARs are of the ␤ 2 -AR subtype. These receptors are localized to ASM (3-4 ϫ 10 4 per cell), epithelium, vascular PHARMACOLOGY AND THERAPEUTICS OF BRONCHODILATORS 453 smooth muscle, and submucosal glands (Ruffin et al, 1982;Carstairs et al, 1985), whereas ␤ 1 -ARs in the lung are confined to glands and alveoli. There is a uniform distribution of ␤-ARs on the alveolar wall with a 2:1 ratio of ␤ 1 /␤ 2 -ARs (Mak et al, 1996).…”
Section: Ethyl]amino]nonyl]piperidin-4-yl] N-mentioning
confidence: 99%